The intersection of near-death experiences (NDEs) and traumatic brain injury (TBI): neurobiological, phenomenological, and creative implications - Iacono, Diego; Feltis, Gloria C. (Frontiers in Human Neuroscience, 2025)
Traumatic brain injury (TBI) and near-death experiences (NDEs) represent profound disruptions in brain function, often associated with dramatic changes in consciousness, self-perception, and behavior. While these events are typically studied for their pathological consequences, a growing body of evidence suggests they may also trigger unexpected cognitive and creative enhancements in a subset of individuals. We explore the intersection between TBI, NDEs, and the emergence of heightened artistic expression, integrating findings from neuroanatomy, neuropathology, genetics, and phenomenology. We examine how alterations in key brain networks - such as the default mode network, frontoparietal circuits, and limbic regions - may underpin shifts in self-awareness, emotion processing, and symbolic thinking, which are frequently reported after NDEs or severe brain trauma. Additionally, we discuss the potential role of neuroplasticity, diaschisis, and compensatory reorganization in facilitating novel patterns of cognition and creative output following injury. Genetic factors potentially influencing susceptibility to such transformations are considered, alongside evolutionary perspectives on why these rare post-injury enhancements may occur. By synthesizing clinical cases, neuroscientific studies, and first-person accounts, we argue that certain brain injuries and altered states of consciousness can function as catalysts for reconfiguration of cognitive and emotional systems, leading to emergent artistic abilities or intensified creative insight. These phenomena challenge traditional dichotomies between damage and function, pathology and creativity, and invite new frameworks for understanding the plastic potential of the human brain. This overview-hypothesis driven article aims to contribute to a deeper understanding of how the mind and brain interact under extreme conditions and how these interactions may unlock hidden reservoirs of human potential. The paper highlights the need for systematic research into post-traumatic and NDE-related cognitive changes, not only to improve clinical outcomes but also to broaden our knowledge of human consciousness and creativity.